Platelet‐type von Willebrand disease: Local disorder of the platelet GPIbα β‐switch drives high‐affinity binding to von Willebrand factor. (19th September 2019) - Tischer, Alexander; Machha, Venkata R.; Moon‐Tasson, Laurie; Auton, Matthew
Abstract: Background: Mutations in the β‐switch of GPIbα cause gain‐of‐function in the platelet‐type von Willebrand disease. Structures of free and A1‐bound GPIbα suggest that the β‐switch undergoes a conformational change from a coil to a β‐hairpin. Objectives: Platelet‐type von Willebrand disease (VWD) mutations have been proposed to stabilize the β‐switch by shifting the equilibrium in favor of the β‐hairpin, a hypothesis predicated on the assumption that the complex crystal structure between A1 and GPIbα is the high‐affinity state. Methods: Hydrogen‐deuterium exchange mass spectrometry is employed to test this hypothesis using G233V, M239V, G233V/M239V, W230L, and D235Y disease variants of GPIbα. If true, the expectation is a decrease in hydrogen‐deuterium exchange within the β‐switch as a result of newly formed hydrogen bonds between the β‐strands of the β‐hairpin. Results: Hydrogen—exchange is enhanced, indicating that the β‐switch favors the disordered loop conformation. Hydrogen—exchange is corroborated by differential scanning calorimetry, which confirms that these mutations destabilize GPIbα by allowing the β‐switch to dissociate from the leucine‐rich‐repeat (LRR) domain. The stability of GPIbα and its A1 binding affinity, determined by surface plasmon resonance, are correlated to the extent of hydrogen exchange in the β‐switch. Conclusion: These studies demonstrate that GPIbα with a disordered loop is binding‐competent and support a mechanism in which local disorder in the β‐switch exposes the LRR—domain of GPIbα enabling high‐affinity interactions with the A1 domain.